Christian Religious Education Paradigm: Learning Efforts for Gifted Students in Schools - Marthen Mau; Suarman Zai; Edwin Goklas Silalahi; Suardin Zai; Saenom Saenom (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
In general, students studying at school have varied talents; There are some students who are academically talented and there are some who are non-academic. The talents that students have can be experienced from birth and can also be experienced through education at school. The aim of writing this article is to provide knowledge or insight into a new paradigm to readers, observers, academics and educational practitioners so that they can understand how to obtain the best solution in developing the education of gifted children with different service models based on Christianity. religious education paradigm. The research method in writing this article is a qualitative descriptive approach using a literature study approach such as books, journal articles and websites on social media as references. The research results show that the contribution of Christian religious education is very influential in developing the potential of talented children. The aspects that are part of the education of gifted children in the Christian religious education paradigm are providing understanding in the form of recognizing talent as a gift from God, moral and ethical development, service and devotion, and spiritual education.